REGENERATIVE LEADERSHIP ROLE IN IMPROVING EXCEPTIONAL PERFORMANCE AMONG SPORTS AND SCOUT ACTIVITY DEPARTMENTS HEADS - Khlood Hameed Abbas (Universitas Negeri Jakarta, 2026)
Background. The Department of Sports and Scouting requires regenerative leadership that motivates staff toward excellence and innovation. Thus, regenerative leadership plays a key role in fostering exceptional performance among sports department heads. Objectives. This research exploring regenerative leadership vital role to improve heads exceptional performance within Departments Sports and Scout Activity. Method. This paper highlights that regenerative leadership surpasses simple skill via concentrating on systemic change, creation besides inspiration to benefit individual also educational institution. Through shifting away from stagnant management styles characterized by stagnation, this type of leadership promotion a long-term vision and a strong message aiming at a accomplishing proficient quality of highest standards. This paper identifying the important problem: the necessity for modernized administrative tactics, which could excellently navigating the sports and scouting environments difficulties. Results. Analysis of data shows that success is deep rooted in the familiar administrative patterns modernization besides deep-seated organizational visions outcome. Results propose that when leaders depended these regenerative qualities, they enable staff and inspire collective decision-making that is significant for institutional feasibility. Conclusion. Focusing on the way leaders consider besides process regeneration, departments could step toward extra supportable in addition to excellent -performing future. Finally, this paper helps as a roadmap for integrating modern administrative techniques to achieve the Directorate of Education strategic purposes.